NOS4A2. Season one [videorecording (DVD)] - O'Brien, Jami (Image Entertainment, 2019)
Charlie Manx, a seductive immortal who feeds off the souls of children, has his whole world threatened when a young woman in New England discovers she has a dangerous gift.